A novel web based application for storing, managing and sharing geotechnical data, illustrated using the national soft soil field testing facility in Ballina, Australia. (January 2018) - Doherty, J.P.; Gourvenec, S.; Gaone, F.M.; Pineda, J.A.; Kelly, R.; O'Loughlin, C.D.; Cassidy, M.J.; Sloan, S.W.
Abstract: This note describes a web based application called "Datamap" that has been developed to address the major challenge of capturing, classifying, organizing and making available geotechnical research data. Datamap is illustrated using an example project at the Australian National Field Testing Facility (NFTF). The example project illustrates the interactive and accessible nature of the web-based application for hosting in-situ and laboratory site investigation data, field testing, construction details, monitoring results, reports and bibliography of related papers.